Federated States of Micronesia : 2006 Article IV Consultation-Staff Report; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that real GDP in the Federated States of Micronesia grew by only 1 1\2 percent in FY2005 and declined by nearly 1 percent in FY2006. The underlying fiscal situation has deteriorated, despite a decline in the overall deficit. Executive Directors have recommended that spending cuts and comprehensive tax reforms be phased in to secure fiscal sustainability. Priority should be given to reducing the public sector wage bill, which is large by regional standards, possibly in the context of a broad reform of the public sector.